1991
DOI: 10.1128/jb.173.6.2141-2145.1991
|View full text |Cite
|
Sign up to set email alerts
|

Myxococcus xanthus protein C is a major spore surface protein

Abstract: Fruiting body formation in Myxococcus xanthus involves the aggregation of cells to form mounds and the differentiation of rod-shaped cells into spherical myxospores. The surface of the myxospore is composed of several sodium dodecyl sulfate (SDS)-soluble proteins, the best characterized of which is protein S (Mr, 19,000). We have identified a new major spore surface protein called protein C (Mr, 30,000). Protein C is not present in extracts of vegetative cells but appears in extracts of developing cells by 6 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…Consistent with our previous results (20), we observed that FibA accumulates specifically in the aggregated cell fraction. The late increase is consistent with the observation that the ϳ31-kDa form of FibA, which represents primarily the two PPC repeats (10), was additionally isolated as the major spore coat protein C (20,31). PilA accumulation is known to increase during development (65), but our analyses indicate that PilA increases specifically in the aggregated cell fraction and remains relatively constant in the supernatant cell fraction.…”
Section: Discussionsupporting
confidence: 77%
“…Consistent with our previous results (20), we observed that FibA accumulates specifically in the aggregated cell fraction. The late increase is consistent with the observation that the ϳ31-kDa form of FibA, which represents primarily the two PPC repeats (10), was additionally isolated as the major spore coat protein C (20,31). PilA accumulation is known to increase during development (65), but our analyses indicate that PilA increases specifically in the aggregated cell fraction and remains relatively constant in the supernatant cell fraction.…”
Section: Discussionsupporting
confidence: 77%
“…We have shown that the MXAN3885 protein is found in the soluble fraction of cells at relatively early times in development, and at later times most of the protein is found in the spore coat. Like other spore coat proteins, such as proteins S, C and U (Gollop et al, 1991;McCleary et al, 1991;Teintze et al, 1985), the MXAN3885-encoded product can be released from mature spores by boiling in 1 % SDS, indicating that while this product may accumulate inside the cell as a soluble protein before sporulation, it is deposited outside the cell during sporulation and can be considered to be a spore coat protein. However, despite significant amino acid sequence similarity between MXAN3885 (strain DK1622) and protein U (strain DZF1), the timing of production of the two proteins differs.…”
Section: Discussionmentioning
confidence: 99%
“…Myxospores were protected by a spore coat that consists mainly of polysaccharides and different proteins (11). Spore coat proteins W, C, S2, and U are synthesized during starvation-induced development, while the spore coat of glycerol-induced spores is composed of proteins S1 and U (6,9,15,16). Purified wild-type and mutant spores prepared by centrifugation on sucrose step gradients (15) showed no significant difference between the numbers of wild-type and mutant spore coat proteins from starvation-and glycerol-induced spores in SDS-PAGE analysis (data not shown).…”
mentioning
confidence: 99%